Emerging Trends in Financial Management: a Technology Driven Approach - Bajpai, Amardeep (AG Volumes, 2024)
Companies now prioritise technological changes in financial management in order to succeed in the digital age. Global banking sector challenges have come from technological innovation and digitalisation. The many studies on new developments in technology-driven financial management techniques are reviewed in this article. This review concluded that the integration of advanced technologies, such as AI-driven financial models and blockchain, is reshaping financial management by enhancing prediction accuracy, risk assessment, and operational efficiency. Digital transformation enables real-time data access, automation, and intelligent decision-making, optimizing financial resources and strengthening security. The digital economy demands a shift from traditional data management to a holistic approach integrating technology with business strategy. By embracing innovation, enterprises can improve internal processes, foster collaboration, and achieve sustainable growth. Intelligent, value-driven financial management is key to navigating the evolving financial landscape, ensuring adaptability, competitiveness, and long-term success in a rapidly digitalizing world.